Infundibula of equine maxillary cheek teeth. Part 1: Development, blood supply and infundibular cementogenesis. (March 2016) - Suske, A.; Pöschke, A.; Schrock, P.; Kirschner, S.; Brockmann, M.; Staszyk, C.
Highlights: Infundibular cementogenesis in equine cheek teeth is documented. Cementogenesis starts in the occlusal aspect of the infundibula. Two main arteries enter each infundibulum in its occlusal aspect. Infundibular blood supply remains vital for a certain period of time after eruption. An explanation for an incomplete cemental filling of the infundibula is proposed. Abstract: There is increasing interest in diseases of infundibula of equine maxillary cheek teeth. Imperfect infundibular cementogenesis has been recognized as an aetiopathological factor for the onset of infundibular necrosis. In this article, infundibular development was examined with particular attention to infundibular blood vessels and cementogenesis. Forty-one deciduous maxillary premolars prior to eruption were investigated using routine histological and immunohistological methods to visualize blood vessels and the enamel organ. Selected specimens were scanned by micro-computed tomography to analyze the three-dimensional configuration of the developing infundibulum. Before eruption, the infundibula are supplied by a central infundibular artery entering the infundibulum from an occlusal direction and by arteries entering the mesial infundibulum from the mesial aspect, and the distal infundibulum from the distal aspect. The central infundibular artery is destroyed shortly after tooth eruption but the lateral arteries remain vital for a time after eruption. As the arteries of the distal infundibulum are located in a more apical position, blood is received for a longer period compared with the mesial infundibulum. Cementogenesis starts first at distinct enamel in-foldings in the occlusal part of the infundibula, advancing in an apical direction. The results suggest a distinct asymmetry between the infundibula with the mesial infundibulum prone to incomplete cementogenesis due to early blood supply cessation.